2020
DOI: 10.3390/cells9092081
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Constrains Rule Metastasis Progression

Abstract: Metastasis formation accounts for the majority of tumor-associated deaths and consists of different steps, each of them being characterized by a distinctive adaptive phenotype of the cancer cells. Metabolic reprogramming represents one of the main adaptive phenotypes exploited by cancer cells during all the main steps of tumor and metastatic progression. In particular, the metabolism of cancer cells evolves profoundly through all the main phases of metastasis formation, namely the metastatic dissemination, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 296 publications
(338 reference statements)
0
12
0
Order By: Relevance
“…The “cell-of-origin” then undergoes clonal expansion, a process that is accompanied by the acquisition of further genetic and phenotypic traits, thereby generating a state of Intra-Tumor Heterogeneity (ITH; [ 118 ]). As a consequence, breast tumors, though clonal in origin, become polyclonal systems [ 119 , 120 ], whereby different clones (i.e., populations of cells that originate from a common ancestor) differ in terms of their genomic and phenotypic profiles [ 121 , 122 , 123 ].…”
Section: Bc Intra-tumor Heterogeneity and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…The “cell-of-origin” then undergoes clonal expansion, a process that is accompanied by the acquisition of further genetic and phenotypic traits, thereby generating a state of Intra-Tumor Heterogeneity (ITH; [ 118 ]). As a consequence, breast tumors, though clonal in origin, become polyclonal systems [ 119 , 120 ], whereby different clones (i.e., populations of cells that originate from a common ancestor) differ in terms of their genomic and phenotypic profiles [ 121 , 122 , 123 ].…”
Section: Bc Intra-tumor Heterogeneity and Metastasismentioning
confidence: 99%
“…The deregulated growth of primary breast tumors is associated with the exhaustion of the local nutrient microenvironment, which leads to progressive nutrient deprivation, the accumulation of waste products and metabolic stress [ 123 ]. A pivotal study on transformed mammary cells revealed that glutamine deprivation strongly fosters the expression of stress-response genes (e.g., ATF4, DDIT3 and XBP1), including inflammatory mediators (e.g., KLF4, CCL2, NF-κB1 and IL20) and it increases the migratory phenotype of tumor cells [ 188 ].…”
Section: Adaptive Responses In Bc Metastasismentioning
confidence: 99%
“…Metastatic progression is based on the ability of cancer cells to acquire an adaptive phenotype disseminating to distant organ sites and evading the immune system. In this context, two comprehensive reviews, proposed by Roda and colleagues [37] and by Benzarti and colleagues [38], examined complementary features of this critical matter, pointing out the ability of cancer cells to gain a bioenergetic shift and discussing the role of metabolic reprogramming in eliciting the metastatization process.…”
Section: Synopsismentioning
confidence: 99%
“…Tumorigenesis represents a dynamic process that induces normal cells to lose their own specific identity and to acquire a series of malignant traits, including deregulated proliferation, evasion of apoptosis and immunosurveillance, and abnormal metabolism [1][2][3]. Notably, this process is driven by two main factors, namely, tumor-specific mutational burden, on one hand, and the continuous interaction of cancer cells with the surrounding stroma, on the other hand [4,5].…”
Section: Introduction: the Heterogeneous Microenvironment Of Tumorsmentioning
confidence: 99%